Analysis of the Impact the Application of the Online Single Submission in the Department of Investment and One Stop Services at Gorontalo Regency - Rion Rinaldi Ibrahim; Titin Dunggio; Rizal (LP2M Universitas Bina Mandiri Gorontalo, 2021)
ABSTRACT In increasing the efficiency of business activities by accelerating business implementation, the government has issued Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services. Based on this policy, all business licensing services are integrated by the center through 1 (one) Electronically Business Licensing System of Online Single Submission (OSS). This research was conducted at the Department of Investment and One-Stop Services, Gorontalo Regency. The purpose of this research was to determine and analyze the effect of Implementing Online Single Submission at the Department of Investment and One-Stop Services, as well as the inhibiting factors. The analysis method used in this research is the qualitative data analysis method, by using interactive models. The data collection used in this research through observation, interviews, and documentation. Based on the research results indicate that Online Single Submission System Implementation whether seen from the aspect of regulatory compliance, coordination, and socialization has not been maximally carried out. Likewise, the inhibiting factors identified in this study, such as the apparatus readiness factor, commitment factor, and supporting facilities that hinder the Implementation of the Online Single Submission System at the Department of Investment and One-Stop Services.